2017
DOI: 10.5152/tjar.2017.200501
|View full text |Cite
|
Sign up to set email alerts
|

Inadverdent Perioperative Hypothermia

Abstract: İ stemsiz perioperatif hipotermi, preoperatif dönemden (anestezi öncesi 1 saat), postoperatif döneme (anestezi sonrası ilk 24 saat) kadar geçen süre içinde vücut sıcaklığının 36°C'nin altına düşmesidir (1). İstemsiz perioperatif hipotermi sıklığının %50-90 aralığında olduğu bildirilmiştir ve cerrahi hastalarının %70'ni etkilediği tahmin edilmektedir. Aynı zamanda istenmeyen klinik sonuçlar, hastanede kalış süresinde uzama ve maliyet artışı ile de birliktedir (2, 3).Köksal ve ark.nın (4) yaptığı bir anket çalış… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
12
0
7
Order By: Relevance
“…Perioperative hypothermia may contribute to delayed recovery and increased postoperative complications such as surgical site infection, major cardiac events, and blood loss[27]. Prevalence of intraoperative and postoperative hypothermia in emergency surgery could be as high as 60% - especially in patients undergoing major abdominal surgery and those receiving the large amount of intravenous crystalloids.…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative hypothermia may contribute to delayed recovery and increased postoperative complications such as surgical site infection, major cardiac events, and blood loss[27]. Prevalence of intraoperative and postoperative hypothermia in emergency surgery could be as high as 60% - especially in patients undergoing major abdominal surgery and those receiving the large amount of intravenous crystalloids.…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%
“…However, there is no significant relationship between perioperative hypothermia and length of hospital stay in critically ill surgical patients[28]. Similar to an elective setting, use of warming techniques such as forced air warming in emergency could reverse or protect against intraoperative hypothermia[27].…”
Section: Application Of Eras Items In Emergency Colorectal Surgery Anmentioning
confidence: 99%
“…In our study, which included 60 patients with total hip replacement surgery, we aimed to evaluate the effect of warming intravenous fluids on hypothermia (‹36⁰C), amount of bleeding, preoperative and postoperative hemoglobinhematocrit changes and amount of blood transfusion. The risk of inadvertent intraoperative hypothermia has been reported in a wide range (50-90%) [8]. Despite the necessary precautions, unpreventable heat loss is a common condition in patients undergoing anesthesia, regardless of the type of anesthesia selected [9].…”
Section: Discussionmentioning
confidence: 99%
“…Even in moderate hypothermia (<35ºC), physiological coagulation mechanisms are impaired, affecting platelet functions and inducing modifications in enzymatic functions. The decrease in platelet activity increases the bleeding and stimulates the need for transfusion [8]. Rajagopalan et al [13] analyzed 14 studies and reported that moderate hypothermia (34ºC -36ºC) increased blood loss by 16% and increased blood replacement rate by 22%.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, active heating methods including forced-air warming (FAW), using electric blankets and radiant heaters, are preferable to passive heating using blankets and drapes. [ 2 5 12 14 15 ]…”
mentioning
confidence: 99%